Unveiling the impact of 16S rRNA gene intergenomic variation on primer design and gut microbiome profiling - Sunthornthummas, Sirinthorn; Wasitthankasem, Rujipat; Phokhaphan, Pimonwan; Sudtachat, Nirinya; Wilantho, Alisa; Ngamphiw, Chumpol; Chareanchim, Wanwisa; Tongsima, Sissades (Frontiers in Microbiology, 2025)
The 16S rRNA gene is crucial for bacterial identification, but primer biases and intergenomic variation can compromise its effectiveness, especially in complex ecosystems like the human gut microbiome. This study systematically evaluates 57 commonly used 16S rRNA primer sets through in silico PCR simulations against the SILVA database. We identified three promising primer sets (V3_P3, V3_P7, and V4_P10) that offer balanced coverage and specificity across 20 key genera of the core gut microbiome. Our findings reveal: (1) significant limitations in widely used “universal” primers, often failing to capture microbial diversity due to unexpected variability in conserved regions, (2) substantial intergenomic variation, even within traditionally conserved regions of the 16S rRNA gene, as demonstrated by Shannon entropy analysis, and (3) discrepancies between intergenomic patterns in NCBI and SILVA databases, highlighting the impact of database choices on taxonomic classification. These results challenge assumptions about 16S rRNA gene conservation and emphasize the need for tailored primer design informed by comprehensive sequence databases. We advocate for a multi-primer strategy to improve coverage and mitigate biases, ultimately enhancing the accuracy and reliability of gut microbiome profiling. This approach has potential applications beyond gut microbiome studies, including animal microbiome research and probiotic community profiling.